Pendidik, Pelajar dan Orangtua, Ketika Kelas Berada dalam Genggaman - Citra Rosalyn Anwar; Rita Gani; Andriani; Nur Fitriani Arkam (Jurnal Riset Public Relations, 2022)
Abstract. Studying from home has become an inevitable choice since the pandemic in early 2020. Classrooms have moved from school buildings to flat screens, both smartphones and laptops. Students, teachers, parents and schools as organizers and important parts of the teaching and learning process, they all have different sides of the story. Technological readiness has not been directly proportional to the readiness of human resources. The “Tular Nalar” Program, which offers solutions to build digital competencies and educators' critical thinking, still has several obstacles. Digital literacy is a mandatory requirement for all parents, educators, schools and students in carrying out learning process from home. This article aims to provide an overview of the teaching and learning process during a pandemic, tular nalar’s role, technology’s role as a new classroom and digital literacy as a necessity for activities in cyberspace. Parents’ readiness is not only in terms of providing learning tools but also understanding devices’ function to complete their position as children’s learning companion at home. On the other hand, educators are also expected to have sensitivity in choosing the most suitable application for each lesson and student's abilities, as well as sufficient digital literacy competence to run maya classes. This article is based on a literature search as a reference and field observations and interviews conducted during the pandemic and the process of “Tular Nalar” program for educators. This article shows the unpreparedness of various parties in carrying out learning from home, both the readiness of infrastructure (networks and devices) and learning tools. Readiness to use available learning applications, and limited digital literacy. Abstrak. Belajar dari rumah menjadi pilihan yang tidak terelakkan sejak pandemi awal tahun 2020. Ruang kelas berpindah dari gedung sekolah ke layar datar baik telepon selular maupun laptop. Siswa, guru, orangtua dan sekolah sebagai penyelenggara dan bagian penting dalam proses belajar mengajar, memiliki sisi cerita yang berbeda. Kesiapan Teknologi belum berbanding lurus dengan kesiapan sumber daya manusia. Program Tular nalar yang menawarkan solusi untuk membangun kompetensi digital dan berpikir kritis pendidik, masih memiliki beberapa kendala. Literasi digital menjadi syarat wajib bagi semua pihak orangtua, pendidik, sekolah dan anak dalam menjalankan proses belajar dari rumah. Artikel ini bertujuan memberikan gambaran proses belajar mengajar di masa pandemi, peran tular nalar, peran teknologi sebagai ruang kelas baru dan literasi digital sebagai sebuah keharusan beraktivitas di dunia maya. Kesiapan orangtua tidak hanya dari sisi penyediaan perangkat pembelajaran tapi pemahaman penggunaan perangkat hingga posisi sebagai pendamping belajar anak di rumah. Sebaliknya pendidik juga diminta memiliki kepekaan memilih aplikasi yang paling sesuai untuk setiap pelajaran dan kemampuan siswa, serta kompetensi literasi digital yang cukup untuk menjalankan kelas dunia maya. Artikel ini berdasarkan pada penelusuran kepustakaan sebagai referensi dan pengamatan lapangan dan wawancara yang dilakukan selama masa pandemi dan proses berjalannya program tular nalar pada pendidik. Artikel ini menunjukkan ketidaksiapan berbagai pihak dalam menjalankan belajar dari rumah, baik kesiapan dari infrastuktur (jaringan dan perangkat) maupun alat belajar. kesiapan penggunaan aplikasi pembelajaran yang tersedia, serta literasi digital yang masih terbatas,